1980
DOI: 10.1136/gut.21.12.1097
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica infection in male homosexuals.

Abstract: Amoebic infection in two male homosexuals is described. The possibility that this infection was acquired through homosexual practices and the implications to clinical and diagnostic services is discussed. Amoebiasis is an uncommon disease in Britain. An estimated 200 new cases of amoebiasis occur annually in England and Wales.1 The disease may be fatal if misdiagnosed or inappropriately treated.2 Most infections are acquired in an endemic area, although occasionally infection has been reported in persons who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In recent years, several reports have appeared concerning the high prevalence of Entamoeba infections in homosexual men living in big cities of Western countries [1][2][3]. Few symptomatic Entamoeba colitis [4] or liver abscess cases [5] are reported in male homosexuals in Western countries, but many studies indicated that no relation was seen between the presence or absence of gastrointestinal symptoms and infection with Entamoeba in male homosexuals [2,3,6,7]. It is reported that zymodeme pattern of Entamoeba isolated from homosexual men in England were non-pathogenic-type I, III and V [6], and nonpathogenic-type I, III and VIII [7].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several reports have appeared concerning the high prevalence of Entamoeba infections in homosexual men living in big cities of Western countries [1][2][3]. Few symptomatic Entamoeba colitis [4] or liver abscess cases [5] are reported in male homosexuals in Western countries, but many studies indicated that no relation was seen between the presence or absence of gastrointestinal symptoms and infection with Entamoeba in male homosexuals [2,3,6,7]. It is reported that zymodeme pattern of Entamoeba isolated from homosexual men in England were non-pathogenic-type I, III and V [6], and nonpathogenic-type I, III and VIII [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1980s, the sexual transmission of E. histolytica was noticed in MSM group who were involved in oral and anal sex. [ 18 ] Since then, it is considered an emerging STI. Several evidences, especially in the last decade, have exposed the signs of sexual transmissibility of E. histolytica .…”
Section: Newly Emerging Sexually Transmitted Infectionsmentioning
confidence: 99%
“…Several groups noted that parasitic infestation was common in gay men who had not travelled to endemic areas. 56,Io2,lo3 Another researcher noticed that an area of Manhattan with a high homosexual concentration had an unusually large number of cases of amebiasis; repeated checks of the water supply revealed no contamination . s7 Unfortunately, reliable figures on the prevalence of these infections among gays are not available, as prevalence studies have been biased by population selection and specimen collection techniques.…”
Section: Parasitic Infectionsmentioning
confidence: 99%